Identifying adverse childhood experiences and mental health needs among a small sample of pregnant women who use cannabis - Jones, Aubrey; Blair, Lisa M.; Kurzer, Julie A.; Rademacher, Kathy; Ducas, Letitia; Cockerham, Cynthia; Ashford, Kristin (Frontiers in Psychiatry, 2025)
IntroductionAs the legalization of cannabis becomes more widespread use has steadily increased. Approximately 5 percent of pregnant individuals self-report use during pregnancy.MethodsThis study uses a mixed methods approach to examine adverse childhood experiences, mental health needs, and cannabis use among a small sample (N =59) of women. Cumulative ACE scores of four or more were considerably high within this sample compared to the US average.ResultsResults of a binary logistic regression indicate an association between ACEs and Cannabis use (OR 1.27, 95% CI (1.002- 1.616) when controlling for maternal age and anxiety. Qualitative results identified two main sub-themes: Medical Use for Mental Health Symptoms and Concerns about Negative Mental Health Effects Postpartum.DiscussionResults suggest a need for patient education about cannabis use in pregnancy and trauma informed care.